Thermal efficiency analysis of the rotary kiln based on the wear of the lining - Zeng, Donghu; Shcherbina, V.Y.; Li, Jiaxiu (Zielona Góra: Uniwersytet Zielonogórski)
The thickness of the lining is reduced from 230 mm to 80 mm due to long-term wear, resulting in low thermal efficiency of the rotary kiln. The thermal resistance, which is positively correlated with the thickness of the lining, is one of the most important factors determining the thermal efficiency of the rotary kiln. The thermal efficiency of the rotary kiln can be improved by introducing insulation material with lower thermal conductivity into the lining.
Keywords: rotary kiln; thermal efficiency; average temperature; heat flux; insulation material